Pengembangan Ejakirna “E-book Jazirah Arab dan Kisah Remaja Nabi Muhammad ” untuk Pembelajaran PAI pada Siswa SD - Munawaroh, Rina; Omala, Siti; Fauziyah, Vina Septiani; Aeni, Ani Nur (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Over time, learning has undergone many changes in accordance with technology and learning history. Therefore, learning must be improved and replaced according to this, so that it has an impact in making learning media that can attract students' attention, especially in PAI learning. Thus, researchers are interested in developing digital-based books or more commonly known as EJAKIRNA (E-book Arabian Peninsula and Prophet Muhammad's Teenage Story) which aims to be a solution to the problems that have been identified. EJAKIRNA (E-book of the Arabian Peninsula and the Story of the Prophet Muhammad's Youth) is an e-book which contains material about the Arabian Peninsula and the story of the Prophet Muhammad from birth to adolescence. This e-book is designed more practically so that it can be used easily by teachers in the implementation of Islamic Religious Education learning in elementary schools. In addition, this e-book is also attractively designed to increase student interest and motivation to learn. This research uses the Design and Development (D&D) development method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The e-book was validated by material experts and design experts, then tested on elementary school students. Data were analyzed using descriptive and statistical techniques. The result of this study is that the E-book